Income Analysis of Local Corn Farming (Zea mays L ) in Tapenpah Village North Central Timor Regency - Umbu Joka; Maria Gradiana Manikin (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2020)
This study aims to : 1) To determine the level of income of corn farming in the village of Tapenpah. 2) To determine the relative profitability of corn farming in Tapenpah Village . This study uses income analysis tools and R/C Ratio. From the results of research it can be known that the total income of the farmers of corn in the village Tapenpah amounting to Rp. . 72,932,416 , 00 with an average of Rp. . 1,072,535.00 . Based on these results, the relative advantage of corn farming in the village of Tapenpah can be profitable with an R/C ratio of 1.82.